Evidence That Rhesus Macaques Self-Cure from a Schistosoma japonicum Infection by Disrupting Worm Esophageal Function: A New Route to an Effective Vaccine? - Xiao-Hong Li; Yu-Xin Xu; Gill Vance; Yun Wang; Long-Bao Lv; Govert J van Dam; Jian-Ping Cao; R Alan Wilson (Public Library of Science (PLoS), 2015)
BACKGROUND:Rhesus macaques are unusual among schistosome hosts, self-curing from an established infection and thereafter manifesting solid immunity against a challenge, an ideal model for vaccine development. Previously, the immunological basis of self-cure was confirmed; surviving worms had ceased feeding but how immunological pressure achieved this was unclear. The schistosome esophagus is not simply a conduit for blood but plays a central role in its processing. Secretions from the anterior and posterior esophageal glands mix with incoming blood causing erythrocyte lysis and tethering and killing of leucocytes. METHODOLOGY/PRINCIPAL FINDINGS:We have analysed the self-cure process in rhesus macaques infected with Schistosoma japonicum. Faecal egg output and circulating antigen levels were used to chart the establishment of a mature worm population and its subsequent demise. The physiological stress of surviving females at perfusion was especially evident from their pale, shrunken appearance, while changes in the structure and function of the esophagus were observed in both sexes. In the anterior region electron microscopy revealed that the vesicle secretory process was disrupted, the tips of lining corrugations being swollen by greatly enlarged vesicles and the putative sites of vesicle release obscured by intense deposits of IgG. The lumen of the posterior esophagus in starving worms was occluded by cellular debris and the lining cytoplasmic plates were closely adherent, also potentially preventing secretion. Seven proteins secreted by the posterior gland were identified and IgG responses were detected to some or all of them. Intrinsic rhesus IgG colocalized with secreted SjMEGs 4.1, 8.2, 9, 11 and VAL-7 on cryosections, suggesting they are potential targets for disruption of function. CONCLUSIONS/SIGNIFICANCE:Our data suggest that rhesus macaques self-cure by blocking esophagus function with antibody; the protein products of the glands provide a new class of potential vaccine targets.